Effectiveness of planned teaching programme on knowledge regarding prevention of urinary tract infection and practice regarding perineal care among mothers of children with urinary tract infection - Hemalatha, L. Anjalin; Sasi, V.; Muthami (Indian Journal of Nursing Sciences, 2024)
Aim: A pre-experimental study was carried out to assess the effectiveness of planned teaching programme on knowledge regarding prevention of urinary tract infection (UTI) and practice regarding perineal care among mothers of children with urinary tract infection in selected hospitals at Puducherry. Method: Thirty five mothers of children with urinary tract infection were selected using the convenient sampling method. The knowledge was assessed using the structured knowledge questionnaire and practice was assessed by an observational check list. Result: Among 35 mothers of children with urinary tract infection in the pre-test, 11% of the mothers of children with urinary tract infection had moderate level of knowledge and 89 % of them had inadequate knowledge regarding prevention of urinary tract infection. In the post test, 51% of the mothers of children with urinary tract infection had moderate level of knowledge and 49% of them had adequate knowledge regarding prevention of urinary tract infection. Conclusion: In the pre-test level of perineal care practice, 3% of the mothers of children with urinary tract infection had adequate practice level, 14% mothers had moderate level and 83% of them had inadequate practice level. In the post-test 97% of the mothers had adequate practice level regarding perineal care and only 3% in moderate level of practice.